EXTENSIFICATION OF FUEL EXCISE: POTENTIALS AND ECONOMIC IMPACTS IN INDONESIA - Setiawan, Prayoga; Gabiela Gumilang; Ayudya Purwani Putri; Muhamad Refkhi Al Aqilah (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2025)
The purpose of this research is to find out the revenue potential and economic impact of imposing an excise tax on RON 90 fuel oil (BBM) in Indonesia. Using the input-output (IO) analysis method and secondary data from the Central Bureau of Statistics and the Ministry of Energy and Mineral Resources, this study analyzes the impact of applying specific excise tariffs of IDR1,000, IDR2,000, and IDR3,000 per liter. The results show that the implementation of excise tax can contribute substantially to state revenue, but also shows significant negative impacts on economic output, gross value added, and labor compensation in various sectors. To mitigate these negative impacts, it is recommended that the additional state revenue be allocated as a stimulus to the affected sectors. The fuel excise policy will be more effective if accompanied by a stimulus policy for the affected sectors through additional government spending, in order to encourage an increase in output and gross value added at the macro level.